The transmission of Mycobacterium tuberculosis in high burden settings - Yates, Tom A; Khan, Palwasha Y; Knight, Gwenan M; Taylor, Jonathon G; McHugh, Timothy D; Lipman, Marc; White, Richard G; Cohen, Ted; Cobelens, Frank G; Wood, Robin; Moore, David A J; Abubakar, Ibrahim (The Lancet infectious diseases, 2016)
Unacceptable levels of Mycobacterium tuberculosis transmission are noted in high burden settings and a renewed focus on reducing person-to-person transmission in these communities is needed. We review recent developments in the understanding of airborne transmission. We outline approaches to measure transmission in populations and trials and describe the Wells–Riley equation, which is used to estimate transmission risk in indoor spaces. Present research priorities include the identification of effective strategies for tuberculosis infection control, improved understanding of where transmission occurs and the transmissibility of drug-resistant strains, and estimates of the effect of HIV and antiretroviral therapy on transmission dynamics. When research is planned and interventions are designed to interrupt transmission, resource constraints that are common in high burden settings—including shortages of health-care workers—must be considered.